Analysis of the Implementation of Good Corporate Governance (GCG) Principles to Improve Service Quality at Bumiputera Syariah Life Insurance Company - Putri, Indry_Anggraini; Syahriza, Rahmi; Rahma, Tri Inda Fadhila (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
In the case of PT AJB Bumiputera 1912, special restrictions are needed because insurance is different from a business established as a PT. This is where the difference is clear: in a PT, this is not always the case, but in a joint venture, the policy will inevitably also seek company investors. This feature involves legal risks as it requires each investor to accept liability for the company incurring losses. As a result, AJB Bumiputera's policyholders are responsible for any business activities that contain the risk of loss and are entitled to a portion of the company's income. The implementation of good corporate governance (GCG) at AJB Bumiputera is the subject of this research. The research method used in this study is qualitative. The findings of this study show that although AJB Bumiputera has tried to implement GCG principles (such as accountability, openness, and fairness), AJB Bumiputera has not implemented it optimally, in other words, the implementation has not been effective.